Why is critical thinking so important in academic life? - Nozima Adxamovna, Mamadjanova (International Journal of Psychosocial Rehabilitation, 2020)
Research has investigated major points of critical thinking in academic life. In this case, both theoretical and methodological analyses were conducted. This article outlines the role of critical thinking in the learning process. Finally, outcomes and shortcomings of the research have been mentioned in the life sciences, and the academy and critical thinking are also stated there as vital factors.